Dwight Bentel Hall 005. - Unknown:::Creator::::::::::::
Photograph shows Dwight Bentel Hall, journalism building. This building was named after Dwight Bentel, a former SJSU journalism professor, in 1982. Bentel founded the journalism program at SJSU and the "Spartan Daily," in 1934.